Differences in the Morphological Characteristics and Body Composition of Football Players FC Trepca ´89 and FC Prishtina in Kosovo - Jovan Gardasevic; Dusko Bjelica; Ivan Vasiljevic; Sami Sermaxhaj; Fitim Arifi (Journal of Anthropology of Sport and Physical Education, 2018)
The aim of this research was to determine the differences among the top football players of the two Kosovo clubs FC Trepca ´89 and FC Prishtina in the morphological characteristics and body composition. A sample of 35 examinees was divided into two sub-samples. The first sub-sample of the examinees consisted of 15 players of FC Trepca ´89 of the average age 21.80±3.57, the champions of the Kosovo Championship in the season 2016/17, while the other sub-sample consisted of 20 players of FC Prishtina of the average age of 24.30±4.99, the vice champions of the Kosovo Championship in the season 2016/17. Football players were tested immediately after the end of the competition season 2016/17. Morphological characteristics (7) in the body composition (4) were evaluated by a battery of 11 variables: body height, body weight, waist size, triceps skin set, biceps skin set, back skin set and abdominal skin set, body mass index, fat percentage, muscle mass and bone mass. The standard central and dispersive parameters of all variables were calculated. The significance of the differences between the players of the top two football clubs in the morphological characteristics and variables for assessing body composition was determined by a t-test for independent samples. It was found that the football players of the two mentioned clubs dont have statistically significant differences by the variables that estimate the morphological characteristics and body composition.